PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. BANK MANDIRI (PERSERO) CABANG DUMAI - Permata Putri, Siti Keumala; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to (1) test and analyze the Leadership Style of Employee Performance at PT. Bank Mandiri (Persero) Dumai Branch, (2) tested and analyzed the influence of Organizational Culture on Employee Performance at PT. Bank Mandiri (Persero) Dumai Branch, (3) tested and analyzed the influence of Leadership Style and Organizational Culture on Employee Performance at PT. Bank Mandiri (Persero) Dumai Branch. This research method uses quantitative descriptive research. The population in this study were employees who worked permanently at PT. Bank Mandiri (Persero) Dumai Branch by taking the entire population as many as 40 employees. Collecting data using a questionnaire and source documents. The data analysis used descriptive analysis and multiple regression analysis. The research results state that: (1) Leadership Style at PT. Bank Mandiri (Persero) Branch Dumai on Employee Performance shows that the leadership implementation carried out by the leader of PT. Bank Mandiri (Persero) Branch Dumai in the good category at 52.5%. (2) Organizational Culture at PT. Bank Mandiri (Persero) Branch Dumai on Employee Performance shows that the Organizational Culture implemented by employees of PT. Bank Mandiri (Persero) Branch Dumai in the good category at 60%. (3) Leadership Style and Organizational Culture simultaneously do not have a significant influence on the Employee Performance of PT. Bank Mandiri (Persero) Branch Dumai which shows that the R square of Employee Performance is influenced by Leadership Style and Organizational Culture of 0.20 or 2% where the remaining 98% is influenced by other factors outside of this study. Key Words: Leadership Style, Organizational Culture